Перетворення RGB зображення з камери в формат HSV - Коротенко, І. В. (ХНУРЕ, 2019)
This message is devoted to the software development for images transformations for computer vision application. The core transformation is RGB->HSV as one of standards for robotic applications. Results can be applied for obstacles detection, recognition and avoiding in mobile robotics.
Keywords: images transformation; RGB; HSV